A shift of political education to the market's needs: A criticism for the development of a value-based political education of Partai Keadilan Sejahtera - Nasiwan Nasiwan (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
This research aims to understand the shifting of political education at Partai Keadilan Sejahtera (Prosperity and Justice Party (PKS). I employ theory of social contract to analyze phenomena involving the elites and the rest of the Muslims. This research is a study of the literature complemented with an in-depth interview with those who involve in the political education either as the subjects or objects of it. The data, then, were analyzed by means of a method of critical discourse. The political education shifting, partly, is related to the shifting of conception on the relationship between Islam, as normative values, and Indonesia, as the context for its implementation. At first, PKS tends to produce a cadre who has strong characters such as a pious cadre and loyal to the party. Majority of the elite party failed to represent themselves at the Parliament. Then, they develop political education which produces activists who are capable of accommodating Islamic values to the political calculation. At last, PKS follows the market demand of middle class Muslims who aspire to produce the religious and modern young Muslim generation. By so doing, PKS is able to expand its political influence amongst the people, especially the Muslim.